2022
DOI: 10.3389/fnut.2022.971666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ancient wheat pasta on gut microbiota composition and bacteria-derived metabolites: A randomized controlled trial

Abstract: Background and aimIn recent years, many studies have suggested that ancient wheat products might have beneficial effects on cardiometabolic risk profile, but little is known about their effect on gut microbiota (GM). The aim of the present study was to evaluate whether a replacement diet with pasta made from ancient wheat (AD) could influence the GM composition and its metabolites’ production compared to a replacement diet with pasta made from modern wheat (CD).MethodsA randomized, double-blinded crossover tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Our study demonstrates that Lachnospiraceae UCG008 can reduce the risk of CD, while Lachnospiraceae UCG010 promotes the development of UC. Limited research has shown that the intake of modern wheat may exert anti-in ammatory effects by increasing the abundance of Lachnospiraceae_UCG-008 spp., promoting butyrate production 45 . Smoking in AS patients increases the abundance of g_Lachnospiraceae_UCG-008, possibly as a manifestation of compensatory anti-in ammatory effects 46 .…”
Section: Forward Mr Analysismentioning
confidence: 99%
“…Our study demonstrates that Lachnospiraceae UCG008 can reduce the risk of CD, while Lachnospiraceae UCG010 promotes the development of UC. Limited research has shown that the intake of modern wheat may exert anti-in ammatory effects by increasing the abundance of Lachnospiraceae_UCG-008 spp., promoting butyrate production 45 . Smoking in AS patients increases the abundance of g_Lachnospiraceae_UCG-008, possibly as a manifestation of compensatory anti-in ammatory effects 46 .…”
Section: Forward Mr Analysismentioning
confidence: 99%